Avaliação da qualidade ambiental e qualidade de vida na bacia hidrográfica do córrego Santa Maria do Leme (São Carlos - SP) - Santana, Raizza Izabel Marcucci (Universidade Federal de São Carlos, 2019)
The relationships between natural and social elements and processes form the complex environmental system. The watershed is configured from a landscape formed by different elements that interact and is considered a complex environmental system, in which the aim is to establish sustainable development that reconciles the quality of life and the environmental quality between the dynamics of the two physical subsystems. natural and socioeconomic. The current urban system remains in unbalanced natural ecological conditions, which reflects on the survival of the community. The city of São Carlos has as the basis of its history a large urban expansion that has been characterized by the precarious living conditions of the low-income population and the creation of closed subdivisions and condominiums occupied by the higher-income population, which has been a challenge to the sustainability paradigm. The use of environmental indicators for quantitative analysis shows us conditions of the urban environment and the living conditions of citizens, which is an instrument of urban management. These indicators were developed by the Organization for Economic Cooperation and Development (OECD), which groups indicators into three groups: pressure, status and response. The objective of this work is to assess the environmental and life quality of the Córrego Santa Maria do Leme Hydrographic Basin, using the OECD methodology with a group of State-only indicators that assess anthropogenic impacts on the environment based on the paradigm of complexity where it was possible to understand the organization and dynamics of the complex environmental system. As shown in the final state index, we can observe a reasonable quality of life and environment at this time, but it is observed that some neighborhoods had low values ​​in several indicators suffering greater impact and being places with more vulnerable income population, so it is necessary that an evaluation is carried out with indicators from the most up-to-date census sector, showing that there are new projects that will be installed in the basin area as well as in the surroundings.
Assessment of environmental quality and quality of life in the Santa Maria do Leme watershed (São Carlos - SP)
Keywords: Sistema Complexo Ambiental; Bacia Hidrográfica; Desenvolvimento Sustentável; Indicadores Ambientais; CIENCIAS BIOLOGICAS